EFEKTIVITAS KOMUNIKASI ANTARPRIBADI MAHASISWA DAN DOSEN PEMBIMBING SKRIPSI - Prininta, Nadia; Sudaryanto, Edy; Jupriono, Jupriono (Universitas 17 Agustus 1945 Surabaya, 2015)
Communication between students and thesis supervisor is a form of interpersonal communication inboth directions, because the communication is done by the students with the thesis supervisor, allowingeach party either students or thesis supervisor giving each response as feedback from the message.Feedback responses can be either verbal or non-verbal language . Effective communication betweenstudents and professors pembibing thesis, is expected to be helped to overcome obstacles or problemsthat occur in the preparation of the thesis. Formulation of the problem in this research is